TEACHING PRACTICAL RESEARCH FOR SENIOR HIGH SCHOOL; AN IN-DEPTH STUDY - Marlyn D. Lucas; Hernando L. Bernal Jr; Mark P. Lucas (Qubahan Academic Journal)
Teaching Practical Research in the Senior High School was a challenge but at the same time a room for exploration. This study investigated the key areas in the interconnected teaching strategies employed to grade 12 students of which are most and least helpful in coming up with a good research output and what suggestions can be given to improve areas that are least useful. It is qualitative in nature and used phenomenological design. Reflection worksheets and interview schedule were the main sources of data.